Evaluation of Well-Type Chamber Calibration Factor for Measurement of Ir-192 Brachytherapy Source Over 10 Institutions: Assef Firnando Firmansyah, Okky Agassy Firmansyah, Sri Inang Sunaryati, Nurman Rajagukguk - Assef Firnando Firmansyah Assef Firnando Firmansyah; Okky Agassy Firmansyah Okky Agassy Firmansyah; Sri Inang Sunaryati Sri Inang Sunaryati; Nurman Rajagukguk Nurman Rajagukguk (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
This paper describes about the evaluation of well-type chamber calibration factor for measurement Ir-192 brachytherapy source. Data were collected at ten institutions that have modalities of Ir-192 brachytherapy. The well-type chamber measures the Ir-192 brachytherapy sources in terms of air kerma strength. Calibration was carried out using the substitution method which adopted from a protocol published by the International Atomic Energy Agency. The well-type chamber standard used was HDR-1000 Plus. The results obtained that NAKS for well-type chamber from PTW manufacturers have a range of values from 9.063 x 105 – 9.875 x 105Gy m2 h-1 A-1 with an average value 9.522 x 105Gy m2 h-1 A-1, while the well-type chamber from Standard Imaging manufacturers have a range of values from 4.634 x 105 – 4.662 x 105Gy m2 h-1 A-1 with an average value 4.648 x 105Gy m2 h-1 A-1. The range of deviations obtained between NAKS new and NAKS old ranges from 0.8% to -1.8%, while the range of normalization results of NAKS new to the average value of NAKS new ranges from 0.952 - 1.029. There was one calibration factor that has a deviation of more than 1% over the NAKS old. Based on the calculation of uncertainty, all the calibration factor results obtained were still within the accepted range.